Quantifying immediate radiative forcing by black carbon and organic matter with the Specific Forcing Pulse - T. C. Bond; C. Zarzycki; M. G. Flanner; D. M. Koch (Atmospheric Chemistry and Physics, 2011)
Climatic effects of short-lived climate forcers (SLCFs) differ from those of long-lived greenhouse gases, because they occur rapidly after emission and because they depend upon the region of emission. The distinctive temporal and spatial nature of these impacts is not captured by measures that rely on global averages or long time integrations. Here, we propose a simple measure, the Specific Forcing Pulse (SFP), to quantify climate warming or cooling by these pollutants, where we define "immediate" as occurring primarily within the first year after emission. SFP is the amount of energy added to or removed from a receptor region in the Earth-atmosphere system by a chemical species, per mass of emission in a source region. We limit the application of SFP to species that remain in the atmosphere for less than one year. Metrics used in policy discussions, such as total forcing or global warming potential, are easily derived from SFP. However, SFP conveys purely physical information without incurring the policy implications of choosing a time horizon for the global warming potential. Using one model (Community Atmosphere Model, or CAM), we calculate values of SFP for black carbon (BC) and organic matter (OM) emitted from 23 source-region combinations. Global SFP for both atmosphere and cryosphere impacts is divided among receptor latitudes. SFP is usually greater for open-burning emissions than for energy-related (fossil-fuel and biofuel) emissions because of the timing of emission. Global SFP for BC varies by about 45% for energy-related emissions from different regions. This variation would be larger except for compensating effects. When emitted aerosol has larger cryosphere forcing, it often has lower atmosphere forcing because of less deep convection and a shorter atmospheric lifetime. A single model result is insufficient to capture uncertainty. We develop a best estimate and uncertainties for SFP by combining forcing results from 12 additional models. We outline a framework for combining a large number of simple models with a smaller number of enhanced models that have greater complexity. Adjustments for black carbon internal mixing and for regional variability are discussed. Emitting regions with more deep convection have greater model diversity. Our best estimate of global-mean SFP is +1.03 ± 0.52 GJ g−1 for direct atmosphere forcing of black carbon, +1.15 ± 0.53 GJ g−1 for black carbon including direct and cryosphere forcing, and −0.064 (−0.02, −0.13) GJ g−1 for organic matter. These values depend on the region and timing of emission. The lowest OM:BC mass ratio required to produce a neutral effect on top-of-atmosphere direct forcing is 15:1 for any region. Any lower ratio results in positive direct forcing. However, important processes, particularly cloud changes that tend toward cooling, have not been included here. Global-average SFP for energy-related emissions can be converted to a 100-year GWP of about 740 ± 370 for BC without snow forcing, and 830 ± 440 with snow forcing. 100-year GWP for OM is −46 (−18, −92). Best estimates of atmospheric radiative impact (without snow forcing) by black and organic matter are +0.47 ± 0.26 W m−2 and −0.17 (−0.07, −0.35) W m−2 for BC and OM, respectively, assuming total emission rates of 7.4 and 45 Tg yr−1. Anthropogenic forcing is +0.40 ± 0.18 W m−2 and −0.13 (−0.05, −0.25) W m−2 for BC and OM, respectively, assuming anthropogenic emission rates of 6.3 and 32.6 Tg yr−1. Black carbon forcing is only 18% higher than that given by the Intergovernmental Panel on Climate Change (IPCC), although the value presented here includes enhanced absorption due to internal mixing.